Impacts of self-confidence cultivation combined with family collaborative nursing on the hope level, stigma and exercise tolerance in patients undergoing radical resection of pulmonary carcinoma - Ye, Fei; Wu, YouHong (Frontiers in Surgery, 2023)
Objective To analyze the impacts of self-confidence cultivation combined with family collaborative nursing on the hope level, stigma and exercise tolerance in patients undergoing radical resection of pulmonary carcinoma. Methods In this expeirment, 79 patients who underwent radical resection of pulmonary carcinoma in our hospital from January 2018 to December 2021, were selected as research objects, and they were divided into two groups according to the date of admission. The control group (n = 39) was given routine care, while the study group (n = 40) was given self-confidence cultivation combined with family collaborative nursing on the basis of the control group. The hope level, stigma, exercise tolerance, and cancer-related fatigue of the two groups were comparatively analyzed. Results The scores of T, P, I dimensions in Herth Hope Inventory (HHI) as well as the total score in the two groups were higher after intervention than before intervention (all P < 0.05).The scores of T, P, I dimensions and total scores of the HHI in the study group were higher as compared with the control group (all P < 0.05). After intervention, the scores of each dimension of the Chinese version of the Lung Cancer Stigma Scale (CLCSS), the modified British Medical Research Council Dyspnea Scale (mMRC), and the scores of each dimension of the Cancer Fatigue Scale (CFS) were lower than before intervention (P < 0.05); the 6-min walk test (6 MWT) result was longer than before intervention (P < 0.05); the scores of each dimension of CLCSS scale, mMRC score, and each dimension of CFS scale in the study group were lower as compared with the control group (P < 0.05) (P < 0.05). Conclusion Self-confidence cultivation combined with family collaborative nursing can promote the hope level of patients undergoing radical resection of pulmonary carcinoma, reduce stigma, enhance exercise endurance, and relieve cancer-related fatigue.